Reflexive Fieldwork Practices in a Sacred Context: Researching the Baduy Religious Landscape - Kusmayani, Anisa Eka Putri; Elfrida, Tuti (Parahyangan Catholic University, 2025)
The growing academic interest in Indigenous communities has led to a surge of studies on the Baduy people in Indonesia. However, many of these studies have been criticized for relying on Western paradigms that misalign with the Baduy’s cosmological, ethical, and relational worldview. This research aims to critically re-examine fieldwork practices in the sacred Baduy context by adopting a decolonial and relational approach that foregrounds methodological sensitivity and epistemic justice. Employing an autoethnographic method, the author reflects on personal experiences conducting collaborative fieldwork with the Baduy community. The study highlights essential elements of Baduy lifeways—including pikukuh, buyut, and principles of asceticism—alongside formal and informal rules that shape engagements with outsiders. The findings underscore the necessity of conducting research that is reflexive and respectful, rooted in the Baduy’s spiritual-relational epistemology. The discussion calls for a rearticulation of research ethics within sacred and Indigenous settings and advocates for pluriversality as a framework to honor diverse ontologies and knowledge systems. This study offers an original contribution by centering Indigenous epistemologies in research methodology and advancing a collaborative model for ethical engagement in sacred landscapes.